Clinical anophthalmos. Issue 8 (August 1987) - O'Keefe, M; Webb, M; Pashby, R C; Wagman, R D
Abstract : We report on 15 patients (10 boys, 5 girls) with clinical anophthalmos. Two of them had bilateral anophthalmos, 10 had systemic anomalies, and six had abnormalities of their remaining eye. Only two appeared to have an associated underlying aetiology. Fourteen patients underwent orbital reconstruction or socket enlargement with varying degrees of success. Our own experience suggests that unnecessary lid procedures should be avoided, but we recommend early prosthetic fittings. We feel that a multidisciplinary approach is necessary to attain useful rehabilitation.